Intelligent Transportation Systems - Y.S.Bhanuteja, B.; Satish, S.; Raviteja, Ch.; Raja Veerendra, y. (International Journal of Engineering and Technology, 2026)
To safeguard environment for future generations and to manage urban complexities like economical and social policies; smart and sustainable cities are necessary, means improving urban planning with affordable housing, adequate water supply, creating green public spaces, upgrading slum settlements, investment in public transport and ensuring access to smart usage of ICT’s for management. And the key segment in smart sustainable city is to have smart buildings, which are built with intelligent management systems and a vision to reduce environmental challenges by higher usage of renewable sources. It is true that, capital cost for smart buildings will be higher than conventional structures but life cycle cost will be very less and even offers increased safety and more quality to the life by which eventually a person and subsequently the society gets benefited. So, accordingly features of smart building can be designed effectively to meet the requirements which are worthy for smart living.